2020
DOI: 10.36660/abc.20200215
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Dados Atualizados e sua Relação Com o Sistema Cardiovascular

Abstract: In December 2019, a new human coronavirus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
32

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 19 publications
0
14
0
32
Order By: Relevance
“…Regarding the diagnosis of COVID-19, several studies suggested the importance of Chest Computed Tomography as an indicator of the disease, but not as a confirmatory test by itself (24,25). Pre-existing cardiovascular conditions were the focus of attention in several publications (26) and also the importance attributed to physical activity as a health affirming and disease prevention measure (27)(28)(29). Several articles concentrated on the analysis of the health measures and care that must be taken when treating dental patients (30,31), as well as on the protection measures of the health personnel involved in the care of patients with COVID-19 (32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the diagnosis of COVID-19, several studies suggested the importance of Chest Computed Tomography as an indicator of the disease, but not as a confirmatory test by itself (24,25). Pre-existing cardiovascular conditions were the focus of attention in several publications (26) and also the importance attributed to physical activity as a health affirming and disease prevention measure (27)(28)(29). Several articles concentrated on the analysis of the health measures and care that must be taken when treating dental patients (30,31), as well as on the protection measures of the health personnel involved in the care of patients with COVID-19 (32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…The wide expression of ACE2 in nerve tissues and the neurotrophic nature of SARS-CoV-2 might render the cardiac nerve fibers a favorite prey (Briguglio et al, 2020a). Severe arrhythmias are nevertheless life-threatening conditions that may occur in over 30% of level 2 patients (Ferrari, 2020) and in higher rates in patients of level 3 (Huang et al, 2020). The prevalence and severity of electrocardiographic changes could reflect the progression of myocardial damage (Guo et al, 2020), but it is very likely that it is associated with disease progression.…”
Section: Electrical Dysregulation Medullary Reflex Alteration and Amentioning
confidence: 99%
“…CARDIOLOGIA E ANGIOLOGIA O acometimento do sistema cardiovascular no indivíduo com COVID-19 é multifatorial e se dá sobretudo em pacientes com fatores de risco cardiovascular ou doença cardiovascular (DCV) preexistente. A infecção produz uma resposta inflamatória exorbitante e pode desencadear lesões não apenas diretas no coração e nos vasos sanguíneos, mas também indiretas pela invasão do vírus nas células endoteliais e pela liberação de citocinas que provocam uma resposta sistêmica aguda (9,10). Foi observado que, com o estado inflamatório desencadeado pelo SARS-CoV-2, há a alteração de alguns marcadores inflamatórios sistêmicos como o D-dímero, a ferritina, a proteína C reativa e a desidrogenase lática, que têm relação direta com o prognóstico dos pacientes (10).…”
unclassified
“…A infecção produz uma resposta inflamatória exorbitante e pode desencadear lesões não apenas diretas no coração e nos vasos sanguíneos, mas também indiretas pela invasão do vírus nas células endoteliais e pela liberação de citocinas que provocam uma resposta sistêmica aguda (9,10). Foi observado que, com o estado inflamatório desencadeado pelo SARS-CoV-2, há a alteração de alguns marcadores inflamatórios sistêmicos como o D-dímero, a ferritina, a proteína C reativa e a desidrogenase lática, que têm relação direta com o prognóstico dos pacientes (10). Os indivíduos com COVID-19 também podem apresentar anormalidades no estado de coagulação sanguínea por diversos mecanismos, como a hipercoagulabilidade por irregularidades nos fatores protrombóticos circulantes, com elevações do fator VIII e do fibrinogênio, além da hiperviscosidade sanguínea (9).…”
unclassified
See 1 more Smart Citation